Modified Huo-Luo-Xiao-Ling Dan Suppresses Adjuvant Arthritis by Inhibiting Chemokines and Matrix-Degrading Enzymes. (7th March 2012) - Nanjundaiah, Siddaraju M.; Lee, David Y.-W.; Ma, Zhongze; Fong, Harry H. S.; Lao, Lixing; Berman, Brian M.; Moudgil, Kamal D.
Abstract : Rheumatoid arthritis (RA) is a chronic inflammatory disease affecting the joints that can lead to deformities and disability. The prolonged use of conventionally used drugs is associated with severe adverse reactions. Therefore, safer and less expensive therapeutic products are continually being sought. Huo-Luo-Xiao-Ling dan (HLXL), a traditional Chinese herbal mixture, and its modified versions possess anti-arthritic activity. In this paper, we examined the influence of modified HLXL on two of the key mediators of arthritic inflammation and tissue damage, namely, chemokines and matrix-metalloproteinases (MMPs) in the rat adjuvant-induced arthritis (AA) model of RA. We treated arthritic Lewis rats with HLXL (2.3 g/kg) by daily gavage beginning at the onset of AA. The control rats received the vehicle. At the peak phase of AA, rats were sacrificed and their draining lymph node cells (LNC) and spleen adherent cells (SAC) were tested. The HLXL-treated rats showed a significant reduction in the levels of chemokines (RANTES, MCP-1, MIP-1 α, and GRO/KC), MMPs (MMP 2 and 9), as well as cytokines (IL-6 and IL-17) that induce them, compared to the control vehicle-treated rats. Thus, HLXL controls arthritis in part by suppressing the mediators of immune pathology, and it might offer a promising alternative/adjunct treatment for RA.